Pengaruh AI-Driven Hyper-Personalization dan Social Media Advertising terhadap Purchase Intention dengan Mediasi Customer Trust - Andi Muhammad Syawqi; Corry Yohana; Ringga Sentagi Asa (Indo Publishing, 2026)
This study aims to analyze the effect of AI-Driven Hyper-Personalization and Social Media Advertising on Purchase Intention, with Customer Trust as a mediating variable, among TikTok Shop Generation Z users in DKI Jakarta. This study employs a quantitative approach using a survey method and Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical technique. The sample consists of 240 respondents, all Generation Z TikTok Shop users in Jakarta, selected through purposive sampling. The data were analyzed using SmartPLS 4.0 software. The results of the analysis indicate that: (1) AI-Driven Hyper-Personalization has a positive and significant effect on Purchase Intention. (2) Social Media Advertising has a positive and significant effect on Purchase Intention. (3) Customer Trust has a positive and significant effect on Purchase Intention. (4) AI-Driven Hyper-Personalization has a positive and significant effect on Customer Trust. (5) Social Media Advertising has a positive and significant effect on Customer Trust. (6) Customer Trust partially mediates the effect of AI-Driven Hyper-Personalization on Purchase Intention. (7) Customer Trust partially mediates the effect of Social Media Advertising on Purchase Intention. These findings indicate that the accuracy of algorithmic personalization, the quality of social media advertising, and the level of user trust in the platform play an important role in driving purchase intention within the social commerce ecosystem. The results of this study are expected to serve as a basis for platform managers and digital marketers in enhancing algorithmic transparency and advertising credibility to support the growth of TikTok Shop among Generation Z.